PERITONEAL DIALYSIS-ASSOCIATED PERITONITIS : A SYSTEMATIC REVIEW - Nur Amelia , Devita (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Peritoneal dialysis is infectious and non-infectious. Peritoneal dialysis causes catheter exit, tube tunnel, and peritonitis. Noninfectious consequences of peritoneal dialysis include catheter malfunction, external leakage, abdominal wall anomalies, scrotal edoema, pleural-peritoneal fistulas, failed ultrafiltration, and encapsulated sclerosis. PD complications include peritonitis. The International Society for Peritoneal Dialysis (ISPD) offers specific recommendations on PD-associated peritonitis prevention and treatment, however clinical practise differs greatly amongst dialysis units. Aim: This article examines the link between peritoneal dialysis and peritonitis and presents its findings. Methods: By evaluating the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 standards, this study demonstrated that it met all of the requirements. This enabled the researchers to ensure that the study was as up to date as feasible. Publications published between 2000 and 2023 were included in the search strategy, which included a variety of electronic reference databases (including Pubmed and SagePub). We did not consider review papers, duplicate publications, or half completed articles. Result: In the PubMed database, the results of our search brought up 133 articles, whereas the results of our search on SagePub brought up 69 articles. The results of the search conducted for the last year of 2000 yielded a total of 20 articles for PubMed and 8 articles for SagePub. In the end, we compiled a total of 21 papers, six of which came from PubMed and three of which came from SagePub. We included nine research that met the criteria. Conclusion: Gram-positive bacteria are the most common cause of Parkinson's disease-associated peritonitis. Despite the high frequency of PD-associated peritonitis, it has a high cure rate.